Portraits of Rural Education: the schooling of residents of the Bom Lugar I Settlement, Upanema - RN - Ana Cleide da Silva de Oliveira; Emerson Augusto de Medeiros; Késia Kelly Vieira de Castro (Universidade Federal do Norte do Tocantins, 2024)
This study's central theme is the schooling of residents of the Bom Lugar I Settlement, Upanema - RN. It started with the following research problem: what is the education level of the residents of Settlement Bom Lugar I, Upanema-RN? It highlights, as a general objective, to investigate, based on a field survey, the schooling of residents of the Bom Lugar I Settlement, Upanema - RN. The research was characterized as a quantitative study, of the field research type. The technique used to produce the data refers to the questionnaire composed of 11 closed and open questions. Fifty residents of Assentamento Bom Lugar I, Upanema - RN participated in the study. As main conclusions, the following stand out: among the factors that contribute to non-schooling in the researched context, emphasis is placed on the lack of school transport, the quality of teaching (decontextualized) at school in the countryside, financial issues, violence in the countryside, the distance from homes to schools and the lack of teachers, many coming from urban spaces.